Redescription of Paromius procerulus (Berg) (new combination) (Heteroptera: Rhyparochromidae: Myodochini), and description of eggs and immature stages - Dellapé, Pablo Matías (Zootaxa, 2005)
Neopamera procerula Berg is transferred to genus Paromius: Paromius procerulus (Berg), new combination. Neopamera sororcula (Berg) is relegated to a junior synonym. The adults are redescribed and illustrated, and the eggs and nymphs are described and illustrated for the first time.